Geophysical investigation of foundation condition of a site in Ikere-Ekiti, Ekiti state, south-western Nigeria (2011)
" A geophysical investigation has been performed using Vertical Electrical Sounding (VES) at a site behind Sammy Guest House in Ikere-Ekiti, Ekiti-State to examine the geophysical parameters that can be used to evaluate the structural competence of the shallow section of the subsurface for construction purposes and building development. The schlumberger configuration was used for the data acquisition. The half- currents electrode (AB/2) was used and the quantitative interpretation of the VES involved partial curve matching and 1-D computer iteration. The field data acquired was presented as geoelectric curves and geoelectric section. The interpretation of the field results showed a significant overburden that is up to 8m. The major subsurface layers are the topsoil (mainly clayey sand and sandy clay), lateritic layer and weathered formation. The northern part of the study area shows the lowest resistivity values that suggest high clay content or possible fracture which have impact on the competence and integrity of the soil construction and building development. Therefore, for building development in the study area, the topsoil must be excavated to a reasonable depth at which the soil is adequately competent and choice of foundation material must take into account the characteristics of the clayed material. "